Modelling User's Location Check-ins on Location-Based Social Networks - Nasirov, Nicat; Albayrak, Songul (IEEE, 2015)
Location-based social networks (LBSNs) have become a popular form of social media in recent years. They provide location related services that allow users to check-in at geographical locations and share such experiences with their friends. Millions of check-in records in LBSNs contain rich information of social and geographical context and provide a unique opportunity for researchers to study user's social behavior from a spatial-temporal aspect, which in turn enables a variety of services including place advertisement, traffic forecasting, and disaster relief. In this paper, we propose a social-historical model to explore user's check-in behavior on KBSNs.
Keywords: data mining; social media; user modelling; probabilistic methods; Engineering; Telecommunications